2021
DOI: 10.1002/bse.2797
|View full text |Cite
|
Sign up to set email alerts
|

Industry 4.0 technologies in the manufacturing sector: Are we sure they are all relevant for environmental performance?

Abstract: This research contributes to the debate about the relevance of Industry 4.0 technologies in improving environmental performance in the manufacturing industry. We employed a qualitative–quantitative approach in which 19 Italian operations managers were interviewed and 260 managers responded to an online questionnaire. The effects of various technologies were ranked using ordinal regression. Comments and suggestions gave context to the quantitative results. Sensors, radio‐frequency identification, artificial int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 62 publications
0
52
0
Order By: Relevance
“…Assessing the opportunities that Industry 4.0 may offer for sustainable development has considerably popular among scholars (Khan et al, 2021). For example, the literature offers deep empirical and theoretical insights into Industry 4.0 implications for sustainable manufacturing (Bag et al, 2021; Chiarini, 2021; Leng et al, 2020), energy sustainability (Ghobakhloo & Fathi, 2021), sustainable supply chain (Luthra et al, 2020), and socioecological sustainability (Stock et al, 2018). Moreover, the implication of Industry 4.0 and digital technologies for the circular economy has received considerable attention (Gupta et al, 2021; Nascimento et al, 2019).…”
Section: Industry 40 and Sustainable Innovationmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessing the opportunities that Industry 4.0 may offer for sustainable development has considerably popular among scholars (Khan et al, 2021). For example, the literature offers deep empirical and theoretical insights into Industry 4.0 implications for sustainable manufacturing (Bag et al, 2021; Chiarini, 2021; Leng et al, 2020), energy sustainability (Ghobakhloo & Fathi, 2021), sustainable supply chain (Luthra et al, 2020), and socioecological sustainability (Stock et al, 2018). Moreover, the implication of Industry 4.0 and digital technologies for the circular economy has received considerable attention (Gupta et al, 2021; Nascimento et al, 2019).…”
Section: Industry 40 and Sustainable Innovationmentioning
confidence: 99%
“…Second, disruptive technologies such as digital twin can massively increase the green product ideation capacities, mainly via dynamic simulation of a new product's entire life cycle (Tao, Cheng, et al, 2018). Thirdly, additive manufacturing, augmented reality, and High‐performance Computing Computer‐aided Design (HPC‐CAD) increase the efficiency of new green product design processes and complex prototyping (Chiarini, 2021; Dev et al, 2020).…”
Section: Industry 40 Function For Sustainable Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as a result, the production system can change its configurations to modify the position of all the machines involved in the manufacture of every single product. This guarantees good-quality products with optimum operational costs [42,98]. Figure 9 shows a comparison of the traditional factory and smart factory.…”
Section: Traditional Vs Smart Factorymentioning
confidence: 99%
“…Proposition 16. To examine the role of digitalization in achieving sustainability through the concept of CE.4.4.5 | Cluster 5: Smart disassemblyAdopting ICT-based tools is important for increasing the value of remanufacturing of products and creates opportunities for business collaboration in the supply chains of returned/used products(Chiarini, 2021;Glöser-Chahoud et al, 2021). Several authors(Blömeke et al, 2020;Charnley et al, 2019;Kerin & Pham, 2019) suggested integrating CPS (Cyber-physical system) to IoT for smart remanufacturing.…”
mentioning
confidence: 99%